New Book Addresses "Lack of Guidance" for the Teaching And Practice of Community-Based Research - Elizabeth Dunens (The University of Alabama, 2022)
Review of the book: Mary Beckman and Joyce F. Long, Community-based Research: Teaching for Community Impact. Sterling, VA: Stylus Publishing, 2016, 360 pages. ISBN: 978-16203635